Download presentation

Published byKellie Hitch Modified over 4 years ago

1
**Definitions: Sum, Difference, Product, and Quotient of Functions**

Let f and g be two functions. The sum of f + g, the difference f – g, the product fg, and the quotient f /g are functions whose domains are the set of all real numbers common to the domains of f and g, defined as follows: Sum: (f + g)(x) = f (x) + g(x) Difference: (f – g)(x) = f (x) – g(x) Product: (f • g)(x) = f (x) • g(x) Quotient: (f / g)(x) = f (x)/g(x), provided g(x) 0 /

2
**Example: Combinations of Functions**

Let f(x) = x2 – 3 and g(x)= 4x Find (f + g) (x) (f + g)(3) (f – g)(x) (f * g)(x) (f/g)(x) What is the domain of each combination?

3
**Example: Combinations of Functions**

If f(x) = 2x – 1 and g(x) = x2 + x – 2, find: (f-g)(x) (fg)(x) (f/g)(x) What is the domain of each combination?

4
**Review For Test 1 Equations of Lines**

Slope of a line, parallel & perpendicular Graph with intercepts, graph using slope-intercept method Formulae for distance and midpoint Graph circle with standard and general form (complete the square) Difference Quotient Piecewise-defined functions Domain & range of a function Intervals where the function increases, decreases, and/or is constant Be able to determine when a relation is a function – ordered pairs or graph Relative Max and Min Average Rate of change Even and odd functions, symmetry Transformations Algebra of functions, domain

5
**The Composition of Functions**

The composition of the function f with g is denoted by f o g and is defined by the equation (f o g)(x) = f (g(x)). The domain of the composition function f o g is the set of all x such that x is in the domain of g and g(x) is in the domain of f.

6
**Example: Forming Composite Functions**

Given f (x) = 3x – 4 and g(x) = x2 + 6, find: a. (f o g)(x) b. (g o f)(x) Solution We begin the composition of f with g. Since (f o g)(x) = f (g(x)), replace each occurrence of x in the equation for f by g(x). f (x) = 3x – 4 This is the given equation for f. (f o g)(x) = f (g(x)) = 3g(x) – 4 = 3(x2 + 6) – 4 = 3x – 4 = 3x2 + 14 Replace g(x) with x2 + 6. Use the distributive property. Simplify. Thus, (f o g)(x) = 3x

7
**Example: Forming Composite Functions**

Given f (x) = 3x – 4 and g(x) = x2 + 6, find: a. (f o g)(x) b. (g o f)(x) Solution b. Next, (g o f )(x), the composition of g with f. Since (g o f )(x) = g(f (x)), replace each occurrence of x in the equation for g by f (x). g(x) = x2 + 6 This is the given equation for g. (g o f )(x) = g(f (x)) = (f (x))2 + 6 = (3x – 4)2 + 6 = 9x2 – 24x = 9x2 – 24x + 22 Replace f (x) with 3x – 4. Square the binomial, 3x – 4. Simplify. Thus, (g o f )(x) = 9x2 – 24x Notice that (f o g)(x) is not the same as (g o f )(x).

Similar presentations

© 2020 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google